Empowering the Disadvantaged Students in Mathematics Education: Relevance of Social Justice, Equity and Mainstreaming - Dhakal, Bed Prasad (Education and Development, 2019)
Mathematical knowledge is indubitable in various sectors, but diversity in culture and tradition in society causes inequality, injustice and backwardness among the students learning mathematics. Study of cultural heritage, customs, behavior in mathematics education is the demand of post-modern paradigm. Efforts of self-organization and co-construction in the initiation of students and teachers through their active participation, interaction and mathematics classroom discourses could be instrumental towards the generation of mathematical knowledge in classroom – which can support to reduce the western domination in mathematics education; and societal negative mind-set about mathematics education will also be minimized in this way. Ethno-mathematics, diversified mathematical strategies, culturally responsive mathematics classroom and enhancing equity in learning mathematics are the major dimensions that mathematics professionals need to exercise for the effective, reflective and contextualized teaching and learning of mathematics. This is a phenomenological study conducted among secondary level mathematics teachers. Using written interview and informal sharing of participants’ experiences towards teaching and learning mathematics, three major themes were developed and discussed. This article primarily shows that there exists the intertwined relation among these themes; and it is essential to properly address these themes for more effective learning of mathematics in the context of Nepalese secondary level classrooms.